Termination of pregnancy in the bitch - DELLIS (Σ. ΝΤΕΛΛΗΣ) S. C.; BOSCOS (Κ. Μ. ΜΠΟΣΚΟΣ) C. M. (Journal of the Hellenic Veterinary Medical Society, 2018)
Unwanted mating is a relatively common occurrence in bitches, often as a result of ignorance or carelessness of owners. Once it has been established that mating has occurred during the fertile stage of the oestrous cycle, there are various options for the prevention of pregnancy. In bitches not intended for future breeding, ovariohysterectomy is the best option. In breeding or potentially breeding bitches a number of treatments have been investigated, but most of them were associated with side effects and complications. This paper focus on currently available methods to prevent or terminate unwanted pregnancy in bitches and emphasizes on dosage, time of intervention, duration, efficacy, and adverse effects of these treatments, as well as on products that could be used and are available in Greece.